Trauma-Informed School Programming: A Partnership Approach to Culturally Responsive Behavior Support - Tessa Bellamy; Govind Krishnamoorthy; Kay Ayre; Emily Berger; Tony Machin; Bronwyn Elizabeth Rees (Sustainability, 2022)
Despite significant investments and reforms, First Nations students have poorer educational outcomes than non-indigenous students. Scholars have pointed to the need to improve the cultural competence of teachers and school leaders, revise punitive and exclusionary disciplinary procedures. and promote the use of culturally responsive practices to mitigate the impacts of colonization, transgenerational trauma and ongoing structural inequities on students. The development of such trauma-informed, culturally responsive systems in schools requires educators to respectfully work in partnership with First Nations communities, as well as health and community services supporting First Nations families. This pilot study evaluates the impact of multi-tier trauma-informed behavior support practices in a regional primary school with a large population of First Nations students. Utilizing a multiple time series, quasi-experimental, within-subjects design, data on the rates of school attendance and problem behaviors were analyzed. Staff knowledge and attitudes related to trauma-informed care were assessed using a self-reporting measure, before and after the two-year implementation of the program. A reduction in behavior difficulties was found, as well as noted improvements in staff reports of knowledge and attitudes. The implications of the findings for the program and future research on culturally responsive practices in schools are discussed.